Greavsie : The Autobiography - Greaves, Jimmy, 1940- (London Time Warner Book, 2003)
In his own characteristically humorous words, Jimmy Greaves tells the story of his life and footballing career, from East End childhood to leading goalscorer in the First Division. He also reveals his dark days - including his battle against alcoholism following his retirement
Include Illustration, Bibliography and Index
Keywords: Soccer players -- England -- Greaves, Jimmy, 1940-